2004
DOI: 10.1107/s0907444903026684
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin binding to jacalin is facilitated by the inherent plasticity of the carbohydrate-binding site: novel mode of lectin–ligand interaction

Abstract: The crystal structure of the complex of meso-tetrasulfonatophenylporphyrin (H(2)TPPS) with jack fruit (Artocarpus integriflora) agglutinin (jacalin) has been determined at 1.8 A resolution. A porphyrin pair is sandwiched between two symmetry-related jacalin monomers in the crystal, leading to a cross-linking network of protein molecules. Apart from the stacking interactions, H(2)TPPS also forms hydrogen bonds, some involving water bridges, with jacalin at the carbohydrate-binding site. The residues that are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
0
23
1
1
Order By: Relevance
“…An alternative approach has been studied and applied using some plant lectins, such as snake gourd Trichosanthes anguina, legume Concanavalin A, and pea lectin, that have been found to bind porphyrins and may have potential application in targeted PDT (3,12,13,14,17,20,22). Our data are the first to demonstrate the porphyrin binding capacity of WGA lectin.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…An alternative approach has been studied and applied using some plant lectins, such as snake gourd Trichosanthes anguina, legume Concanavalin A, and pea lectin, that have been found to bind porphyrins and may have potential application in targeted PDT (3,12,13,14,17,20,22). Our data are the first to demonstrate the porphyrin binding capacity of WGA lectin.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, in order to improve the selective recognition of tumour cells by porphyrins, several plant lectins have been tested as drug delivery agents for these sensitizers (11). Previous spectroscopic and crystallographic studies have shown that some plant lectins (snake gourd Trichosantes anguina seed lectin, concanavalin A, peanut lectin, jacalin) can bind porphyrins (3,12,13,14,17,22,20).…”
Section: Introductionmentioning
confidence: 99%
“…Â прèроді порфірèíè â осíоâíоìу зíàходÿтьсÿ â коìплексі з білкàìè. Тàк, íàпрèклàд, прè обробöі лектèíу Artocarpus integriflora ìезо-тетрà (сульфо-íàтофеíіл) порфірèíоì (H2TPPS) âідбуâàєтьсÿ з'єдíàííÿ ìолекул порфірèíу з білкоâèìè ìолекулàìè з утâореííÿì «білкоâої сіткè» [6]. Порфірèíè здàтíі прèєдíуâàтèсь до ДНК àбо РНК тà âèклèкàтè їх дегрàдà-öію [4,10].…”
Section: тàблèöÿunclassified
“…interestingly, some lectins such as: snake gourd Trichosantes anguina seed lectin, concanavalin A, peanut lectin and jacalin bind photosensitizers (4,9,10,11,13,17,18).…”
Section: Introductionmentioning
confidence: 99%